Urban parks biowaste as a sustainable source of new antidiabetics - Marijan Marijan; Jakupović Lejsa; Vujić Lovorka; Jurić Marina; Končić Marijana Zovko (Acta Pharmaceutica)
Biowaste produced in urban parks is composed of large masses of organic matter that is only occasionally used economically. In this work, extracts of six plants widely distributed in urban parks in Central Europe (Achillea millefolium, Cichorium intybus, Malva sylvestris, Medicago sativa, Plantago lanceolata, and Trifolium pratense), prepared using 10 % and 50 % ethanol, were screened for their antidiabetic and related properties. HPLC and UV-Vis analysis revealed the presence of caffeic acid, quercetin, luteolin, and apigenin derivatives. The extracts were active in DPPH antiradical, β-carotene-linoleic acid, ORAC, and reducing power assay. They inhibited lipoxygenase, collagenase, as well as heat-induced ovalbumin coagulation. They were also able to hinder carbohydrate degradation. For example, IC50 of anti-α-amylase activity of 10 % and 50 % ethanol extract of M. sativa extracts (204.10 ± 2.11 µg mL−1 and 78.27 ± 0.99 µg mL−1, respectively) did not statistically differ from the activity of the positive control, acarbose (284.74 ± 3.81 µg mL−1). Similar results were observed for their anti-α-glucosidase activity. In most assays, the use of 50 % ethanol was shown to be better suited for the extraction of active metabolites. The results indicate that the biowaste obtained from urban parks represents a potential source of plant material for the preparation of high-value antidiabetic products.